Islamic Religious Education Teachers' Strategies in Motivating and Guiding Students Who Experience Quranic Illiteracy at State Junior High School 17, Jambi City - Laila Safitri; Neni Neni (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the strategies employed by Islamic Religious Education (PAI) teachers in motivating and guiding ninth-grade students who experience Qur’anic illiteracy at SMP Negeri 17 Kota Jambi. This research uses a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation involving PAI teachers and students. The findings reveal that teachers apply various strategies, including intrinsic and extrinsic motivation, the use of varied learning methods such as the Iqro’ method, habituation in reading the Qur’an, and individual as well as small-group guidance. Teachers also create a supportive learning environment and apply personal approaches to build students’ confidence. The challenges include low learning motivation, limited instructional time, and lack of family support. To overcome these issues, teachers provide special attention, additional guidance, and utilize simple learning media. In conclusion, the strategies implemented by PAI teachers are fairly effective in gradually improving students’ motivation and ability to read the Qur’an, although further support from various stakeholders is still needed for optimal outcomes.